A protocol for analysing thermal stress in insects using infrared thermography. (February 2016) - Gallego, Belén; Verdú, José R.; Carrascal, Luis M.; Lobo, Jorge M.
Abstract: The study of insect responses to thermal stress has involved a variety of protocols and methodologies that hamper the ability to compare results between studies. For that reason, the development of a protocol to standardize thermal assays is necessary. In this sense, infrared thermography solves some of the problems allowing us to take continuous temperature measurements without handling the individuals, an important fact in cold-blooded organisms like insects. Here, we present a working protocol based on infrared thermography to estimate both cold and heat thermal stress in insects. We analyse both the change in the body temperature of individuals and their behavioural response. In addition, we used partial least squares regression for the statistical analysis of our data, a technique that solves the problem of having a large number of variables and few individuals, allowing us to work with rare or endemic species. To test our protocol, we chose two species of congeneric, narrowly distributed dung beetles that are endemic to the southeastern part of the Iberian Peninsula. With our protocol we have obtained five variables in the response to cold and twelve in the response to heat. With this methodology we discriminate between the two flightless species of Jekelius through their thermal response. In response to cold, Jekelius hernandezi showed a higher rate of cooling and reached higher temperatures of stupor and haemolymph freezing than Jekelius punctatolineatus . Both species displayed similar thermoregulation ranges before reaching lethal body temperature with heat stress. Overall, we have demonstrated that infrared thermography is a suitable method to assess insect thermal responses with a high degree of sensitivity, allowing for the discrimination between closely related species. Highlights: A protocol to obtain thermal variables is presented using infrared thermography. A high number of variables can be obtained from a low number of insect specimens. Individuals are not necessarily killed. PLS regressions disentangle the effects of these correlated variables. Thermal responses of sympatric and closely related dung beetles are discerned.